Two new genera of Eulophinae (Hymenoptera: Eulophidae), including four new species parasitoids on Gracillariidae (Lepidoptera) leaf miners in Costa Rica - Hansson, Christer (Zootaxa, 2024)
Two new genera, Petiolachertus and Macroplectron, each with two new species, P. castor and P. pollux, T. nishidai and T. safron, respectively, are described. Petiolachertus belongs in the tribe Eulophini and Macroplectron in Cirrospilini. Petiolachertus castor, P. pollux and T. nishidai are described from both sexes and have been reared from Gracillariidae leaf miners (unidentified Gracillariidae and Phyllocnistis sp.); T. safron is described from the female only and has been collected through sweeping. The two new genera are diagnosed from other genera in the respective tribes. All material is from Costa Rica.